Quality of life among individuals living with hypertension in urban areas: Gweru - Murepa, Tawanda (Midlands State University, 2019)
Hypertension now largely affects low and middle income countries with a higher prevalence of 46% in African adults of 25 years and above. In Zimbabwe the prevalence of hypertension ranges from 30% and 40% regardless of the cut off and this has been consistent and high in the urban areas than rural areas mostly due to urbanization. The increase in the prevalence rates reported is mostly thought to be attributable to certain unhealthy lifestyles and behaviors such as smoking, excessive alcohol intake. This study aims to determine the quality of life among individuals living with hypertension in urban areas: Gweru. The study was a cross-sectional quality of life (QOL) survey relying on quantitative data. One hundred hypertensive patients aged 18 years and above and those attending the Gweru Provincial Hospital were recruited using simple random sampling technique. Participants were interviewed using a structured questionnaire WHOQOL-BREF (26 items) tools. Descriptive statistics were used to examine mean scores of QOL. Pearson‟s correlation coefficient was applied to estimate the internal consistency, and the level of agreement between different domains of WHOQOL-BREF, respectively. Independent T-test and ANOVA test followed by multiple linear regression analyses were used to measure the association between QOL domains and independent variables. The QOL among hypertensive patients was found moderate in all domains, except for social domain that was fairly low (mean=8.12). Backward multiple linear regressions revealed that being men, married, attainment of higher education, having physical activities at moderate level and employed were positively associated with QOL. WHOQOL-BREF is a reliable instrument to measure QOL among hypertensive patients. The results revealed lower QOL in social relationships domain compared to other domains and differences in QOL across patients‟ demographical characteristics. Given the results, encouraging more in physical activities and strengthening treatment adherence should be considered to improve QOL of hypertensive individuals, especially for social aspect.